A Pacific oyster invasion transforms shellfish reef structure by changing the development of associated seaweeds. (5th April 2020) - Andriana, Rosyta; van der Ouderaa, Isabelle; Eriksson, Britas Klemens
Abstract: Biological invasions are reshaping coastal ecosystems across the world. However, understanding the significance of such invasions is often hampered by the lack of process-based research, resulting in a limited mechanistic comprehension of novel ecological interactions and their consequences. The Pacific oyster ( Crassostrea gigas ) has invaded European coasts, resulting in an astonishing transformation of the intertidal shellfish reef communities in the Wadden Sea; from reefs constructed by blue mussels only ( Mytilus edulis ) to mixed reefs dominated by oysters. Shellfish reefs structure the marine vegetation on soft bottoms by accumulating seaweeds. Nevertheless, assessments of the consequences of the oyster take-over have almost exclusively focused on effects on associated fauna. By constructing small-scale reefs dominated by blue mussels or oysters and following the development of seaweeds over summer, we demonstrated that oysters promoted bloom-forming green algae communities with low primary biomass and low habitat complexity. In contrast, blue mussels promoted the development of meadow-like communities dominated by habitat forming brown seaweeds of the genus Fucus, with high primary biomass and high habitat complexity. An additional field survey showed that increasing numbers of Pacific oysters on a recently invaded natural blue mussel reef significantly decreased the development of the Fucus meadow in spring. Our results indicate that the invasion of oysters may have effects on the structure and function of intertidal reef-communities by changing energy flow and habitat-function. Graphical abstract: Image 1 Highlights: A Pacific oyster invasion transforms the structure of intertidal blue mussel reefs. Native blue mussel reefs promote the development of habitat forming seaweed meadows. Pacific oysters promote green algae mats and decrease the development of the native habitat forming seaweed.